2014
DOI: 10.1111/j.1600-048x.2013.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Parent–environmental interactions shape acoustic signatures in tree swallows: a cross‐fostering experiment

Abstract: Acoustic signatures are common components of avian vocalizations and are important for the recognition of individuals and groups. Th e proximate mechanisms by which these signatures develop are poorly understood, however. Th e development of acoustic signatures in nestling birds is of particular interest, because high rates of extra-pair paternity or egg dumping can cause nestlings to be unrelated to at least one of the adults that are caring for them. In such cases, nestlings might conceal their genetic origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Nestling tree swallows develop an acoustic signature in their begging calls through an interaction between genetic/maternal effects and rearing environment (Reers et al. ), and this brood signature is stronger when nestlings call together than when they call alone (Leonard et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nestling tree swallows develop an acoustic signature in their begging calls through an interaction between genetic/maternal effects and rearing environment (Reers et al. ), and this brood signature is stronger when nestlings call together than when they call alone (Leonard et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…In zebra finches, it remains to be tested using crossfostering experiments whether the brood signature in fledgling begging calls is explained by genetics or if it results from a convergence in call structure. Nestling tree swallows develop an acoustic signature in their begging calls through an interaction between genetic/ maternal effects and rearing environment (Reers et al 2014), and this brood signature is stronger when nestlings call together than when they call alone (Leonard et al 2009). Several bird species show convergence in acoustic structure of vocalizations as a signal of group membership in adults (budgerigars [Hile & Striedter 2000], black-capped chickadees [Nowicki 1989], red crossbills [Groth 1993], and American goldfinch [Mundinger 1980]).…”
Section: Discussionmentioning
confidence: 99%
“…In response to nest parasites, the host nestlings of song sparrow ( Melospiza melodia ) change their begging call to match the parasite [ 31 ]. Apart from these examples in host–parasite systems, one study in tree swallow nestlings ( Tachycineta bicolor ) suggested that brood signature in begging calls just before fledging results from interactions between environment and genetic/maternal effects [ 32 ]. However, to our knowledge, no study has tracked individual ontogeny of begging call structure to demonstrate vocal adjustment in response to social experience.…”
Section: Introductionmentioning
confidence: 99%